MiRNA: Od biogeneze po využití v lékařství - Vlahová, Veronika; Šmerková, Kristýna; Vaculovičová, Markéta; Kizek, René (Journal of Metallomics and Nanotechnologies, 2014)
MicroRNAs are small non-coding RNA molecules that are involved in post-transcriptional regulation of gene expression. They take up about 2 % of the genome and affects up to one third of the protein-coding genes. Their biogenesis starts in the cell nucleus and passes into the cytoplasm where the functional forms of miRNAs participate in the process of RNA interference. Nowadays, the biggest interest focuses on the role of miRNAs during carcinogenesis. Mutations in the genes for various miRNAs types is to promote proliferation and inhibition of apoptosis. Therefore, the miRNA counts as a good diagnostic marker or even as a treatment method.
Keywords: Organelle Biogenesis; biogeneze organel; MicroRNAs; nádory; lidé; mikro RNA; Neoplasms; RNA Interference; Humans; RNA interference